2010
DOI: 10.1152/ajpgi.00037.2010
|View full text |Cite
|
Sign up to set email alerts
|

Damage to the gastric epithelium activates cellular bicarbonate secretion via SLC26A9 Cl/HCO3exchange

Abstract: Gastric surface pH (pH(o)) transiently increases in response to focal epithelial damage. The sources of that increase, either from paracellular leakage of interstitial fluid or transcellular acid/base fluxes, have not been determined. Using in vivo microscopy approaches we measured pH(o) with Cl-NERF, tissue permeability with intravenous fluorescent-dextrans to label interstitial fluid (paracellular leakage), and gastric epithelial intracellular pH (pH(i)) with SNARF-5F (cellular acid/base fluxes). In response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 28 publications
(72 reference statements)
4
38
0
Order By: Relevance
“…The activation of NHE2 might logically be expected to be related to the surface pH change that occurs after damage, and so it was exciting to note that (a) TFF2 null mice have a diminished surface pH increase after damage that was restored by exogenous rTFF3 (25) and that (b) increases in extracellular pH will kinetically activate Na/H exchangers including NHE2 (41). However, we have previously shown that damage causes activation of the SLC26A9 Cl/HCO 3 exchanger to partially mediate an increase in surface pH (30), and we now show that an extracellular pH increase of similar magnitude occurs after damage even in the presence of NHE2 inhibition or NHE2 genetic deletion (Fig. 7).…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…The activation of NHE2 might logically be expected to be related to the surface pH change that occurs after damage, and so it was exciting to note that (a) TFF2 null mice have a diminished surface pH increase after damage that was restored by exogenous rTFF3 (25) and that (b) increases in extracellular pH will kinetically activate Na/H exchangers including NHE2 (41). However, we have previously shown that damage causes activation of the SLC26A9 Cl/HCO 3 exchanger to partially mediate an increase in surface pH (30), and we now show that an extracellular pH increase of similar magnitude occurs after damage even in the presence of NHE2 inhibition or NHE2 genetic deletion (Fig. 7).…”
Section: Discussionsupporting
confidence: 70%
“…Alternatively, NHE2 could be activated by the damage-induced cytosolic acidification, but an EIPA-sensitive acidification was only observed in cells that are fated to be exfoliated from the monolayer (25) and so would not be a viable mechanism in the healthy restituting cells that are the presumed target of TFF-mediated repair. It remains possible that NHE2 in restituting cells is activated in a manner that masks cytosolic or surface pH change via other compensatory mechanisms (18,24,30), but at present, we can only conclude that the apical NHE2 does not mediate its novel beneficial effect on gastric repair via changes in surface pH.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Samples of 4-ml DTCP solution (25,50 or 100 µg/ml) were added to 1.0 ml DPPH methanol solution (1.5x10 -4 M). Following storage at room temperature for 30 min, the absorbance of the solution was determined at 520 nm using a spectrophotometer (UV-5100; Shanghai Metash Instruments Co. Ltd., Shanghi, China), and the remaining DPPH was quantified [(OD DPPH -OD sample )/OD DPPH ]x100%, where OD is optical density.…”
Section: -Diphenyl-1-picrylhydrazyl (Dpph) Free Radical Assaymentioning
confidence: 99%